The complete mitochondrial genome of the Cape honey bee, Apis mellifera capensis Esch. (Insecta: hymenoptera: apidae) - Eimanifar, Amin (Mitochondrial DNA B Resour, 2016)
We characterized the complete mitogenome sequence of the Cape honey bee, Apis mellifera capensis, from South Africa. The circle genome is 16,470 bp in length, with the base composition of 43.2% A, 9.6% C, 5.6% G, and 41.5% T. The assembled mitogenome has 13 protein-coding genes (PCGs), 22 transfer RNAs, two ribosomal RNA genes, and one control region. All protein-coding genes are initiated by ATT, ATC, ATG or ATA codons and are terminated by the typical stop codon TAA. The heavy strand encodes four protein-coding genes, eight tRNAs, and two rRNAs. The light strand encodes nine protein-coding genes and 14 tRNAs. The complete mitogenome sequence of A.m. capensis is identical to the gene arrangement found in other A. mellifera mitogenomes and it provides essential and important DNA molecular data for further phylogenetic and evolutionary analysis of members of the genus Apis.